2015
DOI: 10.5455/aim.2015.23.285-289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharyngeal Space in Different Combinations of Class II Skeletal Malocclusion

Abstract: Objectives:The study was aimed to evaluate the pharyngeal airway linear measurements of untreated skeletal class II subjects with normal facial vertical pattern in prognathic maxilla with orthognathic mandible and orthognathic maxilla with retrognathic mandible.Materials and method:the sample comprised of lateral Cephalograms of two groups (30 each) of class II malocclusion variants. Group 1 comprised of class II malocclusion with prognathic maxilla and orthognathic mandible, whereas group 2 comprised of class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Individuals with impaired nasopharyngeal airways may tend to exhibit mouth breathing due to the enlargement of the adenoid tissue 23. Associated factors may also induce mouth breathing, among which are constriction of the nasal passage, a narrowed or obstructed nasopharynx, hypertrophic nasal membranes, enlarged turbinates, hypertrophic palatine or pharyngeal tonsils, nasal septal deviation, choanal atresia, and pathology in the nose or nasopharynx 4.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with impaired nasopharyngeal airways may tend to exhibit mouth breathing due to the enlargement of the adenoid tissue 23. Associated factors may also induce mouth breathing, among which are constriction of the nasal passage, a narrowed or obstructed nasopharynx, hypertrophic nasal membranes, enlarged turbinates, hypertrophic palatine or pharyngeal tonsils, nasal septal deviation, choanal atresia, and pathology in the nose or nasopharynx 4.…”
Section: Introductionmentioning
confidence: 99%
“…Soni et al compared the mandibular retrognathia to the maxillary prognathia group and reported a difference in oropharynx measurements as a result of the study (22). However, the disadvantage of the findings of this study is that both hypopharyngeal measurements were not made and combined Class II malocclusions were not evaluated.…”
Section: Discussionmentioning
confidence: 80%
“…Class II malocclusions are characterized by the prognathic maxilla, retrognathic mandible, or a combination of these two conditions. It is well known that treatment of Class II malocclusion leads to improved respiratory disturbance due to airway obstruction (22,23). According to Balter, the etiology of Class II malocclusion is the positioning of the tongue backwards and causes discomfort in the cervical region (24).…”
Section: Discussionmentioning
confidence: 99%
“…5 For the normal development and enlargement of craniofacial region, it necessitates the need of a potent airway. 6 Genetics is responsible for the dimensions and proportions of face and hence of the air passages; though, environmental conditions seem to be a foremost cause of nasal obstruction. 7 According to McNamara and Brudon, the upper pharyngeal wall is determined from the posterior surface of the soft palate to the nearest area on the wall of dorsal pharynx, the lower pharyngeal area is determined from the junction of tongue's posterior boundary and the mandible's lower margin to the nearest area on the wall of posterior pharynx.…”
Section: Introductionmentioning
confidence: 99%